Characterization of papillomatosis of the palate in patients with dental prosthesis - Roger Concepción Dago-Infante; Ana Laura Valido-Fra; Daniela Cruz-Sixto; Marlys Susel Sixto-Iglesias; Dunia Milagros Labrador Falero (Universidad Médica Pinareña, 2021)
Introduction: oral diseases constitute a public health problem due to their magnitude and severity. Among them is papillomatous hyperplasia of the palate or grade III sub-prosthetic stomatitis, which is very frequent in edentulous patients with maladjusted removable dental prostheses.